Limited Pledgeability, Asset Prices, and Macroeconomic Fluctuations - Haiping Zhang (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
According to the theory of incomplete contracts, given nonverifiable entrepreneurial project choices together with divergent objectives between an entrepreneur and its outside financier, the entrepreneur can credibly pledge only part of its project outcome for external funding. Meanwhile, entrepreneurial net worth must be put as down payment to ameliorate agency costs. In a real dynamic general equilibrium model with heterogeneous agents and nonverifiable project choices, endogenous agency costs significantly change the businesscycle pattern in the sense that the model can replicate an important empirical fact, the amplified hump-shaped output behavior. Furthermore, variable asset prices can a ect entrepreneurial net worth and then subsequently change the dynamic features of aggregate output along business cycles.
Keywords: E32; G3; E44; 330; Asset Prices; Business Cycles; Credit Constraints; Hump-Shaped Output Dynamics; Nonverifiable Project Choice